MMC-Circuit Model: Tarung Derajat Training to Improve Athletes’ Technical Skills and Discipline - Badai Marganagara Dradjat; Alnedral; Tjung Hauw Sin; Ipang Setiawan; Wahyu Ragil Kurniawan (Universitas Negeri Semarang, 2025)
This study aims to develop and evaluate the effectiveness of the MMC-Circuit Model, a Tarung Derajat training approach designed to improve athletes’ technical skills and discipline. The model is based on the philosophy of Muscle, Mind, and Conscience, integrating technical, physical, and mental components into a structured 12-station circuit training format. The research involved 20 athletes in a small-scale trial and 40 athletes in a large-scale trial over eight weeks. Quantitative results showed significant improvements in athletes’ technical performance, with punching and kicking skills increasing by 19–21%, and a reduction in rule violations by 55%. The model’s overall feasibility was rated 91% (very feasible) by experts. The t-test analysis indicated a significant difference between pretest and posttest results (p < 0.05), while correlation tests showed a strong negative relationship (r = –0.721) between rule compliance and the number of violations. Qualitative feedback revealed enhanced confidence, focus, motivation, and understanding of competition ethics among athletes. These findings demonstrate that the MMC-Circuit Model effectively enhances technical skills, physical readiness, and discipline, while promoting the core values of Tarung Derajat. The model provides a practical, holistic, and sustainable framework for developing athletes in free-fight competitions.